#overtourism on Twitter: a social movement for change or an echo chamber?. Issue 7 (3rd April 2023) - O'Regan, Michael; Choe, Jaeyeon
ABSTRACT: When the linguistic innovation and phrase overtourism was used in an online news report to describe excessive tourism in Iceland in 2016, legacy and social media soon following with in-depth articles and visual representations of perceived excessive tourism in other locations around the world. Given the growing calls for action on overtourism, this study takes a social network analysis (SNA) approach, using a network analysis and visualization software package called NodeXL Pro, to better understand the 10, 325 tweets which used the hashtag 'overtourism' between July 2013 and September 2020. By exploring central users, conversation starters, gatekeepers and influencers, the analysis indicates that an ad hoc network was built around #overtourism on twitter. The analysis indicates that this network is held together by a small number of experts, who play a key role in presenting, distributing and circulating information about this controversial topic. While the studies practical contribution is the use of NodeXL Pro for advanced social media network analysis, the findings also indicate that the ability of these experts to influence perceptions of overtourism inside and outside twitter will depend on whether it can engage broader publics as the tourism sector recovers from a global pandemic.